2019
DOI: 10.1001/jamaoto.2018.2839
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic, Imaging, Audiologic, Clinical, Surgical, and Prognostic Issues in Common Cavity Deformity

Abstract: IMPORTANCECommon cavity deformity is a rare congenital inner ear malformation associated with profound hearing loss and attributed to an early developmental arrest of the cochlear-vestibular structures. This narrative review highlights the need to identify reliable indicators of hearing rehabilitation outcome.OBSERVATIONS Despite its relatively simple definition, common cavity deformity varies widely in morphologic features, presence of cochlear nerve fibers and remnants of Corti organ, and outcome after cochl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 60 publications
(106 reference statements)
0
16
0
Order By: Relevance
“…Although MRI is the gold standard for the identification of the cochlear nerve (CN), 22 it is discussed to be prone to errors 8 . The absence of a clearly visible CN is not appropriately distinguishing between CC and CA because CA may present with a hypoplastic nerve, and CC usually is associated with a common cochleovestibular nerve (CVN) 12,23 . Batuk et al report a case series of 12 children who received auditory brainstem implant after poor hearing outcomes with CI alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although MRI is the gold standard for the identification of the cochlear nerve (CN), 22 it is discussed to be prone to errors 8 . The absence of a clearly visible CN is not appropriately distinguishing between CC and CA because CA may present with a hypoplastic nerve, and CC usually is associated with a common cochleovestibular nerve (CVN) 12,23 . Batuk et al report a case series of 12 children who received auditory brainstem implant after poor hearing outcomes with CI alone.…”
Section: Discussionmentioning
confidence: 99%
“…Different radiological phenotypes are being discussed. The size of the CC varies in previous studies and the limit to other malformations such as incomplete partition type 1 (IP‐1) is not clearly defined 12 …”
Section: Introductionmentioning
confidence: 99%
“…The common cavity is characterized by the absence of the normal differentiation between the cochlea and vestibule with the result of a single cystic cavity (see Figure 1). Common cavity is supposed to be the result of a developmental arrest in the fourth week of gestation and accounts for about 0.7-26% of cochlear malformations [7].…”
Section: Common Cavitymentioning
confidence: 99%
“…Common cavities are assumed to have a non-genetic origin. However, two studies might suggest otherwise: one study found an association between common cavity deformity and autosomal recessive truncating HOXA1(P49639) mutations in an Bosley-Salih-Alorainy syndrome variant [22], another study described the case of a family with two Common cavity is supposed to be the result of a developmental arrest in the fourth week of gestation and accounts for about 0.7-26% of cochlear malformations [7].…”
Section: Common Cavitymentioning
confidence: 99%
See 1 more Smart Citation